Hepatitis B Virus Capsid Assembly Is Enhanced by Naturally Occurring Mutation F97L - Ceres, Pablo (American Society for Microbiology, 2004)
In chronic hepatitis B virus (HBV) infections, one of the most common mutations to the virus occurs at amino acid 97 of the core protein, where leucine replaces either phenylalanine or isoleucine, depending on strain. This mutation correlates with changes in viral nucleic acid metabolism and/or secretion. We hypothesize that this phenotype is due in part to altered core assembly, a process required for DNA synthesis. We examined in vitro assembly of empty HBV capsids from wild-type and F97L core protein assembly domains. The mutation enhanced both the rate and extent of assembly relative to those for the wild-type protein. The difference between the two proteins was most obvious in the temperature dependence of assembly, which was dramatically stronger for the mutant protein, indicating a much more positive enthalpy. Since the structures of the mutant and wild-type capsids are essentially the same and the mutation is not involved in the contact between dimers, we suggest that the F97L mutation affects the dynamic behavior of dimer and capsid.